Functionalized water molecules confined in hydrogels for energy mitigation by assembling liquid nanofoams in micro polymeric pockets. (August 2020) - Zhan, Chi; Li, Mingzhe; Lu, Weiyi
Abstract: In this work, we report the development of an innovative energy dissipative hydrogel. The hydrogel is constructed by assembling liquid nanofoam, composed of hydrophobic nanoporous particles and water molecules, into the polyacrylamide (PAM)-based hydrogel network. Under the hydrostatic loading condition, water molecules are activated and forced into the hydrophobic nanopores. Due to the large surface area of HNPs, substantial mechanical energy is converted into solid-liquid interfacial energy and finally mitigated as heat during liquid flow process. With 1 wt% addition of nanoporous particles, the volumetric energy mitigation capacity of the LN-hydrogel can increase by 300%. Such hydrogel system provides a new paradigm for the design of energy dissipative hydrogels and holds great promise to tissue engineering and regenerative medicine applications. Highlights: Liquid nanofoam system is successfully incorporated into the hydrogel network. Water molecules confined in hydrogel are functionalized by local liquid nanofoam system. The hydrogel exhibits ultrahigh energy mitigation capacity.